Ternary semigroups of topological transformations - Muradov, F.Kh. (KU Publ., 2021)
A ternary semigroup is a nonempty set with a ternary operation which is associative. The purpose of the present paper is to give a characterization of open sets of finite-dimensional Euclidean spaces by ternary semigroups of pairs of homeomorphic transformations and extend to ternary semigroups certain results of L.M. Gluskin concerned with semigroups of homeomorphic transformations of finite-dimensional Euclidean spaces.
Топологиялық түрлендірудің тернарлы жартылайтоптары
Тернарные полугруппы топологических преобразований
Keywords: Euclidean n-space; ternary semigroup; homeomorphic transformations